2016
DOI: 10.7763/ijssh.2016.v6.699
|View full text |Cite
|
Sign up to set email alerts
|

Social Support, Negative Affectivity, and Work Personal Life Balance of Academics

Abstract: Abstract-This study explores the relationship between social support, negative affectivity, and work-personal life balance among academic staff. The sample of this study comprised 70 academics at one faculty in one public higher educational institution in Perak, Malaysia. Quantitative research design using survey questionnaires was utilized for this study. Findings indicated that work-personal life balance is significantly related with social support and negative affectivity. In addition, social support from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Work-life balance was found to be negatively correlated to turnover intention, confirming past research that showed work-life balance decreases turnover intention [10,11,40]. When academics perceive work-life imbalance, it will in turn lead to turnover intention or even actual turnover.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Work-life balance was found to be negatively correlated to turnover intention, confirming past research that showed work-life balance decreases turnover intention [10,11,40]. When academics perceive work-life imbalance, it will in turn lead to turnover intention or even actual turnover.…”
Section: Discussionsupporting
confidence: 82%
“…There are a number of factors that can contribute to turnover intention; two of which are individual"s negative opinions and attitudes toward their job and workplace [37]. Other factors that contribute to intention to leave among academics are bureaucratisation [38] high level of job stress [39] and work-life imbalance [40]. When academics leave, it increases costs on recruiting and training new hires for the university.…”
Section: Turnover Intentionmentioning
confidence: 99%
“…This is consistent with a study of academics in Malaysia that showed that support from coworkers and supervisors predict work-life balance. 48 The assistance provided by colleagues at work, with all the constraints imposed by WFH, seemed to help maintain WLB of employees.…”
Section: Discussionmentioning
confidence: 99%
“…Working relationships were also found to be negatively impacted by homeworking, with superficial connections with colleagues, workplace exclusion, and concerns about commitment to work being some of the key reasons for this impact. Wider occupational literature also states the importance of work/team level social support on productivity (eg, 27 ) and work-life balance (eg, 28 , 29 ). As a result, it is recommended that line managers and employers should be proactive in encouraging and providing time for team and organization social activities as a non-mandatory activity.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%